Self-assembled monolayers of perfluoroanthracenylaminoalkane thiolates on gold as potential electron injection layers - Zhang, Zibin; Wächter, Tobias; Kind, Martin; Schuster, Swen; Bats, Jan W.; Nefedov, Alexei; Zharnikov, Michael; Terfort, Andreas (ACS applied materials & interfaces, 2016)
As a material with relatively small band gap and low lying valence orbitals, perfluoroanthracene (PFA) is of interest for the modification of electrode surfaces, for example, as charge injection layers for n-type organic semiconductors. To covalently attach PFA in the form of self-assembled monolayers (SAMs), we developed a synthesis of derivatives with a sulfur termination, linked to the 2-position of the PFA moieties by an −NH- group and a short alkane chain with two and three methylene groups, respectively. Spectroscopic characterization of the SAMs reveals that the molecules adopt an almost upright orientation on the gold surface, with the packing density mostly determined by the steric demands of the PFA units. The number of the methylene groups in the −NH-alkyl linker has only a minor impact on the SAM structure because of the nonsymmetric attachment of the PFA units, which permits the compensation of the orientational constraints imposed by the bending potential. The investigated SAMs alter the work function of gold by +(0.59-0.64) eV, suggesting comparably strong depolarization effects, affecting the extent of the work function modification.